Interaksi Ke Transaksi: Kontribusi Kredibilitas Seller dalam Mempengaruhi Keputusan Pembelian Produk Elektronik di Marketplace - Wisesa, I Ketut Ari Pramana; Pika, Putu Ayu Titha Paramita (Masyarakat Ekonomi Syariah Bogor, 2025)
This study aims to analyze the effect of Live Shopping and Buy Now Pay Later (BNPL) on consumer purchase decisions, with Seller Credibility as a moderating variable. A quantitative approach was applied by distributing questionnaires to respondents who had purchased electronic products through the Shopee platform. Data were analyzed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method. The results reveal that Live Shopping and BNPL have a positive and significant influence on consumer purchase decisions. Furthermore, Seller Credibility moderates the relationship between Live Shopping and purchase decisions, and strengthens the effect of BNPL on purchase decisions. These findings suggest that marketing strategies based on interactive engagement and flexible payment methods effectively enhance consumers’ purchase intentions and decisions on e-commerce platforms.